1998
DOI: 10.1136/gut.42.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole induces altered bile acid metabolism

Abstract: Background-It has been reported that the acidity of gastric contents could be an important factor in regulating jejunal flora. Aims-To investigate the eVects of omeprazole induced changes in gastric pH on jejunal flora and bile acid metabolism. Methods-Twenty one patients with gastric ulcer and 19 healthy volunteers were studied. Deconjugation of bile acids was detected using a bile acid breath test. Jejunal fluid was aspirated using a double lumen tube with a rubber cover on the tip and deconjugation was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 29 publications
5
53
0
2
Order By: Relevance
“…This concerns viridans streptococci, coagulase-negative staphylococci, Haemophilus sp., diphtheroids, Moraxella sp., lactobacilli, and other streptococci, most of which are Gram-positive bacteria. With dedicated measures anaerobic species of oral origin are also recovered [66].…”
Section: Gastric Acidity and The Composition Of The Gastric Microfloramentioning
confidence: 99%
“…This concerns viridans streptococci, coagulase-negative staphylococci, Haemophilus sp., diphtheroids, Moraxella sp., lactobacilli, and other streptococci, most of which are Gram-positive bacteria. With dedicated measures anaerobic species of oral origin are also recovered [66].…”
Section: Gastric Acidity and The Composition Of The Gastric Microfloramentioning
confidence: 99%
“…If a PPI fails to suppress gastric acid, then unconjugated bile salts may diffuse into the epithelial cells and cause mucosal metaplasia. Pharmacologically, hypochlorhydria induced by daily PPI use produces periods during the day in which pH of the gastric juice is at or near a neutral pH levels 30. A study by Shindo et al .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Shindo et al . showed that hypochlorhydria can induce major changes in the gastric flora and affect the pH of small bowel fluid to allow bacterial overgrowth 30. Moreover, the Shindo et al .…”
Section: Discussionmentioning
confidence: 99%
“…46 Moreover, approximately 20% of the population do not possess these bacteria as a component of their colonic micro-biota, and the growing use of antibiotics further lessens the sensitivity of this test. 46 Additionally, it is well known that changes in the diet, 47,48 including the ingestion of antacids and proton-pump inhibitors, 49 can indeed alter the profile of gut flora. Thus, a negative HBT may be due to a shift from hydrogen to methanogen-producing bacteria.…”
Section: Methods For Assessing Small Intestinal Functionmentioning
confidence: 99%